Pengaruh Job Stress Kerja Dan Work Life Balance terhadap Kepuasan Kerja Karyawan Shift Malam di RSUD KHZ Musthafa Singaparna Tasikmalaya - Anggi Ibnu Ramdani; Herdiyanti Herdiyanti (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study investigates the critical factors influencing job satisfaction among night shift employees at RSUD KHZ Musthafa Singaparna Tasikmalaya, given the inherent challenges of 24-hour hospital operations. Night shift workers are particularly susceptible to physical and psychological strain, which can elevate job stress and disrupt work-life balance, ultimately threatening their job satisfaction. The research employs a quantitative associative approach, utilizing Likert-scale questionnaires distributed to 75 night shift staff selected through purposive sampling. Data were analyzed using Multiple Linear Regression with SPSS. Instrument validation confirmed that all items were both valid and reliable. Partial regression results reveal that job stress exerts a positive and significant effect on job satisfaction (t = 3.106, Sig. = 0.003), while work-life balance also demonstrates a positive and significant impact (t = 1.815, Sig. = 0.044). Simultaneously, both variables together significantly influence job satisfaction (F = 10.121, Sig. < 0.001), with an RSquare of 0.419, indicating that 41.9% of the variance is explained by the model, while 58.1% is attributable to external factors. These findings underscore the importance for hospital management to actively manage job stress through targeted interventions and design equitable shift scheduling policies. Such strategies are essential to sustaining high levels of employee satisfaction, which in turn supports both staff well-being and the quality of patient care in a demanding healthcare environment.